Дiя радiацiйних сил звукового поля на сферичну частинку в околi плоскої межi рiдини - Жук, О.П. (Видавничий дім "Академперіодика" НАН України, 2008)
The influence of the radiation force on a spherical particle in the vicinity of the plane boundary of a liquid is investigated. Dependences of the force on the ratio of densities, the distance to the boundary, and the parameters of the acoustic field are established.